2018
DOI: 10.1155/2018/1483041
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Ameliorates Doxorubicin-Induced Cardiotoxicity in Swiss Albino Mice by Modulating Oxidative Damage and Cellular Inflammation

Abstract: Thymoquinone is the active constituent of Nigella sativa, having antioxidant and anti-inflammatory actions. In present study, we have analyzed the effects of thymoquinone on doxorubicin (DOX) induced cardiotoxicity in mice. In this experiment, thirty mice (25–35 gm) were divided into five groups (Groups A, B, C, D, and E) each containing six animals. Normal saline was given to a control group (Group A) for 14 days. Cardiotoxicity was induced by DOX (15 mg/kg, i.p.) in Group B, once on the 13th day of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…However, the treatment with aqueous Murraya leaf extract increases SOD and catalase level suggesting its antioxidant and ROS-scavenging nature. Not only the present study but also many previous studies on the protective effect against doxorubicin-induced cardiotoxicity based on the antioxidant property have shown a similar effect on SOD and the catalase activity [47,48,51,52,54]. Total antioxidant status of the doxorubicin-treated animals was greatly reduced in the present study suggesting that doxorubicin treatment causes depletion of antioxidants in the body.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 78%
See 3 more Smart Citations
“…However, the treatment with aqueous Murraya leaf extract increases SOD and catalase level suggesting its antioxidant and ROS-scavenging nature. Not only the present study but also many previous studies on the protective effect against doxorubicin-induced cardiotoxicity based on the antioxidant property have shown a similar effect on SOD and the catalase activity [47,48,51,52,54]. Total antioxidant status of the doxorubicin-treated animals was greatly reduced in the present study suggesting that doxorubicin treatment causes depletion of antioxidants in the body.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 78%
“…leaf extract significantly reduced the lipid peroxidation suggesting the antioxidant potential of the plant. Many previous studies on natural products or other compounds with high amount of antioxidants have shown a reduction of lipid peroxidation in doxorubicin-induced cardiotoxicity [27,51,52,54,55].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Serum myocardial enzymes (AST, LDH, CK and CK-MB) are the important indexes that reflect the extent of myocardial injury ( 18 ). As presented in Table III , DOX significantly increased the activity of all enzymes compared with controls, indicating cardiotoxicity.…”
Section: Resultsmentioning
confidence: 99%